Earnings management and deferred tax / Rohaya Md Noor, Nor'Azam Mastuki and Zanariah Aziz - Md Noor, Rohaya; Mastuki, Nor'Azam; Aziz, Zanariah (UPENA, 2007)
This study investigates whether firms use deferred tax expense to meet earnings targets: (1) to avoid an earnings decline and (2) to avoid a loss. The current study replicates Phillips et al. (2003 )'s study, where they found evidence that firms use deferred tax expense to manage earnings. The study examines the financial statements prepared for 2001 - 2003 of firms from consumer and industrial products listed on the first and second board of Bursa Malaysia. The final sample comprises of 493 firm-years base on the deferred tax expense reports for the three-year investigation periods, after filtering the outliers at Is' and 99th percentiles. Using Burgstahler and Dichev (1997) earnings distribution approach, Healy (1985) total accruals and Modified Jones model abnormal accruals (Dechow et al., 1995), the study finds evidence that firms use deferred tax expense to avoid a loss. This study also evidenced an increasing trend of deferred tax liabilities reported by firm from 1990 - 2004. The credit balance of deferred tax liabilities means firms report book income higher than taxable income, which indicates the firms' tax planning strategies by crystallizing their tax liabilities to the future years.